Factors influencing consumer's intention towards e-grocery shopping: An extended technology acceptance model approach - Winda Trisna Ryadi; Florentina Kurniasari; Kristianus Ade Sudiyono (Economics, Management and Sustainability)
The e-grocery industry in Indonesia is multiplying and is expected to become one of the most important markets in the world. Massive amount of funding for e-grocery start-ups, the high desire of Indonesian consumers to buy grocery products online, and COVID19 are increasing the growth of e-grocery services in Indonesia. Although the desire to use e-grocery services in Indonesia is high, data shows that e-grocery adoption is still far below other e-commerce product categories such as fashion and electronics. Previous research and surveys also show that consumers will return to shopping for wholesale products offline and stop/reduce the use of e-grocery after the COVID19 pandemic. Therefore, this research is interested in examining the factors that can increase the adoption of e-grocery in Indonesia. Quantitative research was conducted using the purposive sampling method and obtained 135 respondents who have ever used e-grocery service/shopping in the JABODETABEK area. Data were analyzed using PLS-SEM (Partial Least Square – Structural Equation Model). The results of this study indicate that perceived risk has a negative effect on Trust. Social Influence, Perceived Usefulness, and Perceived Ease of Use have a positive effect on Trust. Social Influence and Perceived Ease of Use have a positive effect on Perceived Usefulness. However, it turns out that Trust in this study was not proven to affect the intention to use e-grocery services/shopping for grocery products online.